Atmospheric deposition of mercury and cadmium impacts on topsoil in a typical coal mine city, Lianyuan, China - Liang, Jie; Feng, Chunting; Zeng, Guangming; Zhong, Minzhou; Gao, Xiang; Li, Xiaodong; He, Xinyue; Li, Xin; Fang, Yilong; Mo, Dan (Chemosphere (Oxford), 2017)
Mercury (Hg) and cadmium (Cd) in the atmosphere from coal combustion emissions play an important role in soil pollution. Therefore, the purposes of this study were to quantitatively evaluate the atmospheric Hg and Cd deposition and to determine the influence of atmospheric deposition on Hg and Cd contents in surface soil in a typical coal mine city. Atmospheric deposition samples were collected from May 2015 to May 2016 at 17 sites located in industrial, agricultural and forest areas in the Lianyuan city. Atmospheric Hg and Cd deposition fluxes in the different land use types showed high variability. Curvilinear regression analysis suggested that the atmospheric Hg deposition fluxes were positively related with Hg contents in soils (R2 = 0.86359, P < 0.001). In addition, atmospheric Cd deposition fluxes were also positively correlated with Cd contents in soils when the site LY02, LY04 and LY05 (all belong to agricultural land) were not included in the fitting (R2 = 0.82458, P < 0.001). When they were included, there was no significant relationship between them (R2 = 0.2039, P = 0.05). The accumulation of Hg and Cd concentration in topsoil due to the influence of atmospheric deposition will increase rapidly in the next 30 years, and the mean value of the increment will reach 2.6007 and 33.344 mg kg−1. After 30 years, the Hg and Cd concentration will increase slowly. The present study advocates that much attention should be paid to the potential ecological hazards in soil resulting from the atmospheric Hg and Cd deposition. [Display omitted] •Investigating atmospheric deposition fluxes of Hg and Cd in a typical coal mine city.•Hg and Cd pollution was serious in surface soils.•Atmospheric Hg and Cd deposition fluxes were positive correlated with soil Hg and Cd concentrations.•It is predicted that the increment of Hg and Cd contents in topsoil was caused by atmospheric deposition.